No, the null hypothesis will be, there is no difference between the mean scores of campus 1 and campus 2.
Therefore, the null hypothesis would be:
H₀: µ₁ - µ₂ = 0
where µ₁ is the population mean score of campus 1 and µ₂ is the population mean score of campus 2.
What is mean by Subtraction?Subtraction in mathematics means that is taking something away from a group or number of objects. When you subtract, what is left in the group becomes less.
Now, We test this null hypothesis against the alternative hypothesis that the mean score on campus 1 is higher than on campus 2:
Hₐ: µ₁ > µ₂
Hence, if there is sufficient evidence to reject the null hypothesis and conclude that there is a significant difference between the mean scores of campus 1 and campus 2.
Thus, No, the null hypothesis will be, there is no difference between the mean scores of campus 1 and campus 2.
Therefore, the null hypothesis would be:
H₀: µ₁ - µ₂ = 0
where µ₁ is the population mean score of campus 1 and µ₂ is the population mean score of campus 2.
Learn more about the subtraction visit:
https://brainly.com/question/17301989
#SPJ2
Sam and Brett share £54 in the ratio of 5:4 how much does each person get
You are traveling to Chicago for a job interview. You leave Toledo, Ohio, at 5:45 A.M. and arrive in Elkhart, Indiana, at 8:15 A.M.. The distance from Toledo to Elkhart is 136 miles; the distance from Toledo to Chicago is 244 miles. The speed limit is 65 mph. What is the minimum speed you must maintain in order to arrive in Chicago before 10:30 A.M.
PLEASE PLEASE HELP ME?!?!!? PLEASSEE I ONLY HAVE 2 QUESTIONS!!!
When the function f(x) = 6(9)x is changed to f(x) = 6(9)x + 1, what is the effect?
Select one:
a. There is no change to the graph because the exponential portion of the function remains the same.
b. All input values are moved 1 space to the right.
c. The x-intercept is 1 space higher.
d. The y-intercept is 1 space higher.
Evaluate fourth root of 9 multiplied by square root of 9 over the fourth root of 9 to the power of 5 . (5 points)
Select one:
a. 9 to the power of negative 1 over 2
b. 9 to the power of negative 1 over 4
c. 9
d. 92
1. Changing f(x) to f(x) + 1 adds 1 to every output value of the function, moving that value "1 space higher". This is true for the y-intercept, too.
___
2. The rules of exponents apply:
a^b · a^c = a^(b+c)1/a^b = a^-bYou apparently want to simplify ...
... 9^(1/4) × 9^(1/2) / 9^(5/4)
... = 9^(1/4 + 1/2 - 5/4)
... = 9^((1+2-5)/4)
... = 9^(-2/4) = 9^(-1/2)
if 12 1/2% of a sum of money is $40 what is the total sum of money?
The total sum of money will be $320.
Let the total sum of money be represented by x.
Based on the information given, the equation to solve the question will be:
12 1/2% × x = 40
0.125x = 40
Divide by 0.125
x = 40/0.125.
x = 320
Therefore, the total sum of money will be $320.
Read related link on:
https://brainly.com/question/2805223
simplify leaving your answer with positive exponents.
Find the midpoint of the segment with the given endpoints. P(–2, 1) and Q(–3, 2)
Answer:
(-5/2, 3/2)
Step-by-step explanation:
The midpoint is the average of the coordinates of the endpoints:
(P +Q)/2 = ((-2, 1) +(-3, 2))/2 = (-2-3, 1+2)/2 = (-5/2, 3/2)
These tables of values represent continuous functions. In which table do the values represent an exponential function?
A.
x y
1 3
2 6
3 9
4 12
5 15
B.
x y
1 2
2 6
3 18
4 54
5 162
C.
x y
1 10
2 22
3 34
4 46
5 58
D.
x y
1 7
2 8
3 9
4 10
5 11
Answer:
The correct option is B.
Step-by-step explanation:
A function is called an exponential function if it has common ratio.
A function is called an linear function if it has common difference.
In option A.
[tex]\frac{f(2)}{f(1)}=\frac{6}{3}=2[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{9}{6}=\frac{3}{2}[/tex]
[tex]2\neq \frac{3}{2}[/tex]
Since the given table has different ratio, therefore it is not an exponential function. Option A is incorrect.
In option B.
[tex]\frac{f(2)}{f(1)}=\frac{6}{2}=3[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{18}{6}=3[/tex]
[tex]3=3[/tex]
Since the given table has common ratio, therefore it is an exponential function. Option B is correct.
In option C.
[tex]\frac{f(2)}{f(1)}=\frac{22}{10}=\frac{11}{5}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{34}{22}=\frac{17}{11}[/tex]
[tex]\frac{11}{5}\neq \frac{17}{11}[/tex]
Since the given table has different ratio, therefore it is not an exponential function. Option C is incorrect.
In option D.
[tex]\frac{f(2)}{f(1)}=\frac{8}{7}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{9}{8}[/tex]
[tex]\frac{8}{7}\neq \frac{9}{8}[/tex]
Since the given table has different ratio, therefore it is not an exponential function. Option D is incorrect.
Answer:
Table B represents an exponential function.
Step-by-step explanation:
An exponential function is a function which has common ratio. Using this fact we will evaluate the functions given in the form of a table.
Table A.
f(1) = 3
f(2) = 6
f(3) = 9
Now [tex]\frac{f(2)}{f(1)}=\frac{6}{3}=\frac{2}{1}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{9}{6}=\frac{3}{2}[/tex]
Ratios are not equal so it's not an exponential function.
Table B.
f(1) = 2
f(2) = 6
f(3) = 18
[tex]\frac{f(2)}{f(1)}=\frac{6}{2}=\frac{3}{1}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{18}{6}=\frac{3}{1}[/tex]
Here ratios are same therefore it's an exponential function.
Table C.
f(1) = 10
f(2) = 22
f(3) = 34
[tex]\frac{f(2)}{f(1)}=\frac{22}{10}=\frac{11}{5}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{34}{22}=\frac{17}{11}[/tex]
Ratios are not equal therefore it's not an exponential function.
Table D.
f(1) = 7
f(2) = 8
f(3) = 9
[tex]\frac{f(2)}{f(1)}=\frac{8}{7}[/tex]
[tex]\frac{f(3)}{f(2)}=\frac{9}{8}[/tex]
Ratios are not equal so it's not an exponential function.
Therefore Table B is the correct option.
find the measure of the requested angle. find the complement of 41*
Find the measure of the requested angle. find the complement of 41°.
Solution:
The Sum of Complementary Angles is 90°.
So, Sum of Requested Angle and Given Angle =90°
So,Requested Angle+Given angle=90°
So,Requested Angle+41°=90°
To find, Requested Angle we subtract 41° from both sides,
Requested Angle+41°-41°=90°-41°
Requested Angle+0°=49°
So, Requested Angle=49°
Answer:49°
Find m/AEB
A.
10
B.
70
C.
110
D.
170
Find the number of ways that an organization consisting of 15 members can elect a president, a treasurer, and q secretary. (assuming no person is elected to more than one position)
Total Members = 15
For electing present number of members = 15
For electing treasurer the numbers of members =14
For electing secretary the numbers of members =13
Find the numbers of possible ways for election of members= ?
Possible ways for election =15*14*13
=2730
Marko is buying carpet for his bedroom floor. His room measures 13 feet by 12 feet. How many square feet of carpet will Marko need to cover the floor in his room?
Answer: 156 square feet of carpet would be needed to cover the floor in his room.
Step-by-step explanation:
Since we have given that
Dimensions of his room as follows :
Length of his room = 13 feet
Width of his room = 12 feet
We need to find the square feet of carpet which is used to cover the floor of his room.
so, we just need to find the area of his room.
Area of rectangle = Length × Breadth
So, Area of his room becomes
[tex]13\times 12\\\\=156\ sq.\ feet[/tex]
Hence, 156 square feet of carpet would be needed to cover the floor in his room.
Factor completely 56a2b3 − 35ab.
7ab(8ab2 − 5)
7a(8b2 − 5ab)
Prime
7a(8ab3 − 5b)
Answer:
7 ab ( 8 ab² - 5 ) .
Step-by-step explanation:
Given : 56 a²b³ − 35 ab.
To find : Factor completely.
Solution : We have given 56 a²b³ − 35 ab.
Taking 7ab common form both terms .
7 ab ( 8 ab² - 5 ) .
Therefore, 7 ab ( 8 ab² - 5 ) .
each of 5 boys ate 2/3 of a pizza. what is the total amount of pizza the boys ate?
We have that for the Question "each of 5 boys ate 2/3 of a pizza. what is the total amount of pizza the boys ate?" it can be said that each boy ate
Pt=3.333pizzaFrom the question we are told
each of 5 boys ate 2/3 of a pizza. what is the total amount of pizza the boys ate? total amount of pizza the boys ateGenerally the equation for the total amount of pizza the boys ate is mathematically given as
Pt=N*Ratio
Therefore
Pt=5*2/3
Pt=3.333pizza
For more information on this visit
https://brainly.com/question/19007362
a player gets to throw 4 darts at the target shown. Assuming the player will always hit the target, the probability of hitting an odd number three times is *blank* times more than the probability of hitting an even number 3 times
Answer: The probability of hitting an odd number three times is [tex]3\dfrac{3}{8}[/tex] times more than the probability of hitting an even number 3 times.
Step-by-step explanation:
From the given picture , the total total number of sections in the spinner = 5
Sections having Odd numbers = 3
Sections having Even numbers =2
We know that , [tex]\text{Probability}=\dfrac{\text{Favorable outcomes}}{\text{Total outcomes}}[/tex]
So , probability of hitting an odd number = [tex]\dfrac{3}{5}[/tex]
Probability of hitting an even number = [tex]\dfrac{2}{5}[/tex]
Since all events are independent of each other ,
So , probability of hitting an odd number three times = [tex](\dfrac{3}{5})^3=\dfrac{27}{125}[/tex]
Probability of hitting an even number three times = [tex](\dfrac{2}{5})^3=\dfrac{8}{125}[/tex]
Divide [tex]\dfrac{27}{125}[/tex] by [tex]\dfrac{8}{125}[/tex] , we get
[tex]\dfrac{27}{125}\div\dfrac{8}{125}\\\\=\dfrac{27}{125}\times\dfrac{125}{8}=\dfrac{27}{8}=3\dfrac{3}{8}[/tex]
Hence, the probability of hitting an odd number three times is [tex]3\dfrac{3}{8}[/tex] times more than the probability of hitting an even number 3 times.
Answer:
3.375
Step-by-step explanation:
shorty's gross pay last week was $251.20.if her hourly rate was $7.85,how many hours did she works?
Which summation formula represents the series below?
13 + 9 + 5 + 1
The sum of the series is 28.
The series 13 + 9 + 5 + 1 is an arithmetic series with a common difference of -4. To express this in summation (sigma) notation and find its sum, we first identify the first term (a1) as 13 and the common difference (d) as -4.
Next, we determine the number of terms (n). The series decreases by 4 each time, so we find the number of steps it takes to go from 13 to 1, which are 4 terms in total (13, 9, 5, 1).
We can write the summation formula for an arithmetic series as Sn = n/2 * (2a1 + (n-1)d), where Sn is the sum of the first n terms. With n = 4, a1 = 13, and d = -4, we plug these into the formula:
S4 = 4/2 * (2(13) + (4-1)(-4))
S4 = 2 * (26 - 12)
S4 = 2 * 14
S4 = 28
The sum of the series is 28.
Today a clothing store took 30% off the price of a dress, and for the next 3 days, it will take 30% off the previous day's price. If the price of the dress yesterday was $300.00, what will be the price of the dress 3 days from now?
Answer:72.03
Step-by-step explanation:
A triangle has interior angles measuring 40 and 52. Which triangle are similar to this triangle? select true or false for each triangle.
Find the length and width of a rectangle that has the given area and a minimum perimeter. area: a square centimeters
if the surface area of two smilar spheres is 256 feet and 576 feet, what is the ratio of the volume of the smaller sphere to the volume of the largee sphere
The ratio of the volume of the smaller sphere to the volume of the larger sphere, given their surface areas are 256 ft² and 576 ft², is 8:27.
The student has asked about finding the ratio of the volumes of two similar spheres given their surface areas. The surface areas are 256 ft² and 576 ft². To find the volume ratio, we need to use the fact that the ratio of the surface areas of similar spheres is the square of the ratio of their radii, and thus the ratio of the volumes will be the cube of the ratio of their radii.
Let's denote the surface areas as S₁ and S₂, and the volumes as V₁ and V₂. Then, S₁:S₂ = (radius of smaller sphere)² : (radius of larger sphere)² and V₁:V₂ = (radius of smaller sphere)³ : (radius of larger sphere)³.
First, we find the square root of the surface area ratios: [tex]\sqrt{\frac{256}{576} }[/tex] = [tex]\frac{16}{24}[/tex] = [tex]\frac{2}{3}[/tex]. Then, taking the cube of [tex]\frac{2}{3}[/tex] gives us the volume ratio V₁:V₂ = [tex](\frac{2}{3} )^3[/tex] = [tex]\frac{8}{27}[/tex].
Therefore, the ratio of the volume of the smaller sphere to the volume of the larger sphere is 8:27.
When designing a building, you must be sure that the building can withstand hurricane-force winds, which have a velocity of 73 mi/h or more. The formula f=0.004av^2 gives the force F in pounds exerted by a wind blowing against a flat surface. A is the area of the surface in square feet, and v is the wind velocity in miles per hour. How much force is exerted by a wind blowing at 81 mi/h against the side of the building shown?
The first step is calculate the surface area of the flat surface shown
Surface area of the rectangle = length * width = 25*12.9 = 322.5 square feet
Surface area of the triangle = 1/2 *base*height = 1/2*25*7.2 = 90 square feet
Total surface area = 322.5 +90 = 412.5 square feet
Total force = 0.004*a*v^2 = 0.004*412.5*81^2 = 10,825.65 pounds
hey can you please help me posted picture of question
If f(x)=4x-6 and g(x) =2x find f(x) •g(x)
Please help me I need help
PLZ HELP ASAP CIRCLES
Circle 1 is centered at (5,8) and has a radius of 8 cm. Circle 2 is centered at (1,-2) and has a radius of 4cm. The circles are similar because you can translate circle 1using the transformation rule (___,___) and then dialate it using a scale factor of (___).
how do I do this question 4x-2=6
12+5v=2v-9 please show step by step!
To get it, combine like terms and restrain the variable. Segregating both sides by 3 gives the solution to the equation as v = -7.
How to solve the expressionTo solve the condition 12 + 5v = 2v - 9, take after these steps:
Step 1: Segregate the variable terms on one side of the condition and the steady terms on the other side.
Subtract 2v from both sides to move the variable term to the cleared outside:
12 + 5v - 2v = 2v - 9 - 2v
Alter both sides of the condition:
12 + 3v = -9
Step 2: Separate the variable term by moving the reliable term to the other side.
Subtract 12 from both sides to move the dependable term to the proper side:
12 + 3v - 12 = -9 - 12
Unwind both sides of the condition:
3v = -21
Step 3: Light up for v by confining both sides of the condition by the coefficient of v, which is 3.
Portion by 3 to clarify for v:
v = -21 / 3
Streamline the division:
v = -7
The solution to the equation is v = -7.
Learn more about expression here:
https://brainly.com/question/1859113
#SPJ6
Marcus baked a loaf of banana bread for a party. He cut the loaf into equal size pieces. At the end of the party, there 6 pieces left. Explain how you can find the number of pieces in the whole loaf if Marcus told you that 1/3 of the loaf was left.
The equation of a circle is (x−2)^2+(y−16)^2=169 . What is the circle's radius?